IMPLEMENTASI MANAJEMEN SUMBER DAYA TENAGA KEPENDIDIKAN DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN AGAMA ISLAM PADA SISWA - Catur Wulandari (UNISAN JURNAL, 2024)
So for this situation the creators need to analyze how to run the teacher board’s assets in working on the nature of Islamic school administration at MIN 9 bandar Lampung . Implementation of instructor asset administration, for example, regulates educators who teach according to their teaching foundation, around S.1, gifted in utilizing learning techniques and media, creating educator skills by involving instructors in reforms and workshops, inspiration to continue coaching, awarding awards to outside educators normal and giving authority to educators who require discipline and terrible performance, involving educators in every school improvement, recognizing and fostering educator thinking and abilities, completing direct supervision exercises over the training of educators, as a result of educators evaluating execution immediately followed up, concentrating entirely on special instructors.